2001
DOI: 10.1007/s100510170278
|View full text |Cite
|
Sign up to set email alerts
|

Collective quantum tunneling of strongly correlated electrons in commensurate mesoscopic rings

Abstract: We present a new effect that is possible for strongly correlated electrons in commensurate mesoscopic rings: the collective tunneling of electrons between classically equivalent configurations, corresponding to ordered states possessing charge and spin density waves (CDW, SDW) and charge separation (CS). Within an extended Hubbard model at half filling studied by exact numerical diagonalization, we demonstrate that the ground state phase diagram comprises, besides conventional critical lines separating states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In this paper, we demonstrated that, in families of carbon‐based chains, most stable members of one parity (even or odd) are singlets while most stable members of the opposite parity (odd or even) are triplets. This is a sui generis effect qualitatively different from other even–odd effects known from studies over decades in other areas …”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…In this paper, we demonstrated that, in families of carbon‐based chains, most stable members of one parity (even or odd) are singlets while most stable members of the opposite parity (odd or even) are triplets. This is a sui generis effect qualitatively different from other even–odd effects known from studies over decades in other areas …”
Section: Resultscontrasting
confidence: 79%
“…Noteworthily, the even-odd singlet-triplet alternation 25 extensively discussed in this paper is qualitatively different from all other even-odd effects (e.g., in multilayers, 26 self-assembled monolayers, 27 quantum dot arrays, [28][29][30][31] molecular electronic devices 2,3 ) known since the early days of quantum mechanics. [32][33][34][35] In those cases, it is merely a certain property rather than the very nature of the ground state that exhibits alternation.…”
Section: Introductionmentioning
confidence: 61%
“…Such ensemble averages have been demonstrated to be relevant for nanoclusters. 20 Although there have been numerous studies of phase separation and similar phenomena in Hubbard systems, 16,21 in our opinion, thermal properties and phase instabilities of small Hubbard clusters at an arbitrary filling have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…4 are described by Hamiltonians H(ε g ) possessing a particlehole (or charge conjugation) symmetry (see, e. g., Ref. 13 and citations therein) around ε g = 0: H h (ε g ) = H(−ε g ). That is, the zero-bias conductance g(+ε g ) = g(−ε g ) (as well as other relevant properties not considered in Ref.…”
Section: Constraints For N-type and P-type Conductionmentioning
confidence: 99%